Between Humanity and Technology: Speculative Reflections on Cyborg Migration—Insights from The Waste Tide and Poor Things - Lu, Yahui; Mydin, Raihanah Mohd (Forum for Linguistic Studies, 2025)
The fast growth of digital technology has resulted in new types of migration, most notably the migration of cyborgs—entities that combine human and machine components. Speculative fiction serves as a reflective lens, illuminating the potential tensions inherent in the evolving relationship between humans and machines. This study investigates the socio-environmental implications of cyborg migration through the narratives of The Waste Tide by Chen Qiufan and Poor Things by Alasdair Gray. In The Waste Tide, a near-future China is depicted where electronic waste scavengers are transformed into cyborgs, mirroring the anxieties around exploitation, environmental degradation, and the fight for cyborg rights amidst technological advancement. This narrative encapsulates the struggle for identity and agency in a world where boundaries between humans and machines blur, revealing the complexities of coexistence. Conversely, Poor Things reimagines Victorian society through cyborg-like beings, addressing societal fears while underscoring the necessity for inclusive policies that acknowledge both human and nonhuman perspectives. By analyzing these texts, this article explores the emerging challenges faced by cyborg refugees, the requisite legal and institutional frameworks to navigate such migrations, and strategies to enhance acceptance and inclusivity in urban environments. Ultimately, this research contributes to the discourse on humane migration approaches in the digital era, emphasizing the intricate interplay between technology, culture, and environmental sustainability.